2012
DOI: 10.4081/gi.2012.e4
|View full text |Cite
|
Sign up to set email alerts
|

Complications of percutaneous endoscopic gastrostomy-jejunostomy for levodopa/carbidopa infusion in advanced Parkinson's disease

Abstract: Continuous infusions of levodopa directly into the duodenum-yeyunum is an effective therapy to reduce daily off time in an advanced stage of Parkinson's disease, but it is not without complications, particularly device related problems. We present our experience in three Spanish hospitals with these complications, including a severe case with migration, several decubitus ulcers, and one case of perforation of the bowel and finally death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…The patient required intestinal resection and died from postoperative complications [7] . Olivares et al [8] reported the case of a patient with mechanical small bowel obstruction. The investigation revealed multiple ulcerations in the duodenum and jejunum and the fistulization of the tube through the jejunal wall into the mesenteric root.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient required intestinal resection and died from postoperative complications [7] . Olivares et al [8] reported the case of a patient with mechanical small bowel obstruction. The investigation revealed multiple ulcerations in the duodenum and jejunum and the fistulization of the tube through the jejunal wall into the mesenteric root.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate surgery was required which showed multiple areas of intestinal perforation. The patient died after 2 days [8] . The same authors described a case of a large antro-duodenal ulcer due to the pressure of the jejunal tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are few reports of decubitus ulcer caused by PEG-J tube. [13][14][15] Nevertheless, several cases of small bowel perforation caused by jejunal extension tube have been published. [16][17][18] We assume that decubitus ulcer is seldom recognized early and is diagnosed when it causes perforation, because most of those who maintain enteral feeding via PEG-J are not able to complain of ulcer symptoms.…”
Section: 11mentioning
confidence: 99%
“…The risk factors for bezoar formation include a history of gastric surgery, ingestion of fiber-rich foods, and suffering from systemic diseases, such as hypothyroidism and diabetes mellitus (4). Phytobezoar associated with LCIG is a rare device-related complication that forms compressive erosion, ulcerative lesions, and fistulas due to tube extension in the gastrointestinal tract and can be fatal at times (5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%